Economic analysis of cocoyam production in Ghana - Boakye-Achampong, Stanley (2017)
A thesis submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the award of the Degree of Master of Philosophy in Agricultural Economics.